Functional and morphological response of the dog colon to ischaemia. Issue 10 (October 1972) - Robinson, J. W. L.; Rausis, C.; Basset, P.; Mirkovitch, V.
Abstract : Total ischaemia of loops of dog colon was induced by clamping all afferent arteries and the colonic wall for different periods of time. Net sodium transport across the mucosa is abolished after one hour's ischaemia, but Na + -K + -ATPase levels in microsomal suspensions from the mucosa only fall significantly after two hours' ischaemia. Studies on the functional and morphological recovery of colons subjected to three hours' ischaemia have disclosed an extremely heterogeneous response among the 24 dogs used. Although all parameters were non-existent 24 hours after the intervention, one colon revealed a morphological and functional recovery one week after the operation, whilst two, three, and three out of six recovered after two, three, and four weeks respectively. There was a good correlation between the functional and macroscopic appearance of these recovered loops, though histologically various degrees of disorganization of the mucosa were observed. Among the loops that had no function, there was also a considerable variation in their microscopic structures. The level of Na + -K + -ATPase in the mucosa was found to be a faithful indicator of the functional state of the tissue, and could be closely correlated with the morphological findings.